Adolescent depression symptoms and e-cigarette progression. (1st November 2021) - Moustafa, Afaf F.; Testa, Shannon; Rodriguez, Daniel; Pianin, Stephen; Audrain-McGovern, Janet
Abstract: Background: Depression symptoms are associated with the initiation of cigarette smoking and progression to regular use. Whether similar relationships exist between depression symptoms and adolescent e-cigarette progression has not been firmly established. Methods: This prospective longitudinal survey study measured the relationship between depression symptoms and e-cigarette use among 1822 adolescents from four public high schools outside of Philadelphia, PA. Adolescents completed in-classroom surveys at wave 1 (fall 2016, 9th grade) and 6-month intervals for the following 36 months (fall 2019, 12th grade). E-cigarette use, depression symptoms, and potential covariates were measured at each wave. A latent growth curve model was used to assess the longitudinal relationship between e-cigarette use and depression symptoms. Results: Baseline depressive symptoms had a significant effect on e-cigarette use trend (b = 0.01, z = 4.29, p < 0.0001) while holding other variables constant. A standard deviation increase in depressive symptoms at baseline was associated with a 0.25 standard deviation increase in the rate of e-cigarette progression across the following 36 months. By contrast, the path from baseline e-cigarette use to depressive symptoms trend was not significant ( p = 0.74). Conclusions: The present study provides new evidence for the effects of depression symptoms on adolescent e-cigarette progression. Greater depressive symptoms at age 14 years old were associated with a faster rate of e-cigarette escalation. However, e-cigarette use was not related to the development of depression symptoms over time. It will be important to examine whether adolescents with elevated depression symptoms respond similarly to e-cigarette prevention campaigns as adolescents in general. Highlights: Depression symptoms predicted more rapid e-cigarette progression in adolescents. E-cigarette use was not associated with an escalation in depression symptoms. Depression screening may aid in identifying those at risk of e-cigarette progression. These findings from adolescents in PA should be replicated in a national sample.